Sistem pendidikan Mesir dan perbandingannya dengan Indonesia - Sulaiman, Sulaiman; Rusdinal, Rusdinal; Gistituati, Nurhizrah; Ananda, Azwar (Ta'dibuna: Jurnal Pendidikan Islam, 2021)
This study describes the contemporary education system in the Republic of Egypt. Since the revolutionary era of 1952, Egypt has sought to expand access to education opportunities for the community as a prerequisite for the country's social and economic development. In this study, a literature review was conducted to obtain and describe Egyptian educational information based on references from various sources. The results show that Egypt has an education system with two parallel structures, namely the secular structure and the religious structure of Al-Azhar. The secular structure is regulated by the ministry of education while the religious structure of Al-Azhar by the ministry of Al-Azhar affairs or commonly referred to as the ministry of religion in other countries. In the description of this article, it can be seen the similarities and differences between the education system in Egypt compared to Indonesia. Each country's education system has advantages and disadvantages, so the two countries can take each other's best practices to be adopted and taken into consideration in the development of the education system. Abstrak Penelitian ini menggambarkan sistem pendidikan kontemporer yang ada di Republik Mesir. Sejak era revolusi tahun 1952, Mesir mengupayakan perluasan kesempatan akses terhadap pendidikan bagi masyarakat sebagai pemenuhan prasyarat dalam pembangunan sosial dan ekonomi negara. Dalam penelitian ini, literature review dilakukan untuk memperoleh dan mendeskripsikan informasi pendidikan Mesir berdasarkan referensi dari berbagai sumber. Hasil penelitian menunjukkan Mesir memiliki sistem pendidikan dengan dua struktur paralel, yaitu struktur sekuler dan struktur keagamaan Al-Azhar. Struktur sekuler diatur oleh kementerian pendidikan sementara struktur keagamaan Al-Azhar oleh kementerian urusan Al-Azhar atau biasa disebut sebagai kementerian agama di negara lain. Dalam uraian artikel ini dapat dilihat kesamaan dan perbedaan antara sistem pendidikan di Mesir dibandingkan dengan Indonesia. Masing-masing sistem pendidikan Negara tersebut memiliki kelebihan serta kekurangan, maka kedua negara bisa saling mengambil best practice untuk diadopsi dan dijadikan bahan pertimbangan dalam pengembangan sistem pendidikan.